AB0240 MMP-3 as A Biomarker of Disease Activity of Rheumatoid Arthritis. (15th July 2016) - Kumagai, S.; Uemura, Y.; Saito, T.; Umeda, R.; Muta, A.; Izumi, M.; Abe, K.; Sendo, S.; Tsuji, G.
Abstract : Background: Measurement of serum MMP-3 levels has been considered useful to estimate the disease activity of rheumatoid arthritis (RA). We have shown that serum MMP-3 was significantly correlated with DAS28 (CRP) and could be a useful marker in predicting joint destruction 1, 2 . CXCL13 attracts CXCR5-expressing B and helper T cells to the follicle and probably has central roles of ongoing immune activation in RA development 3 . Serum MMP-3 and CXCL13 have been reported as biomarkers for detecting the disease activity and predicting the therapeutic outcomes of RA 4 . Objectives: The aim of this study is to confirm the clinical significance of serum MMP-3 and CXCL13 measurement in the evaluation of disease activity and prediction of therapeutic outcome in RA patients treated with biologics. Methods: Serum MMP-3 was serially measured by MMP-3 Latex kit (Sekisui Medical Co.) for 146 RA patients before and after treatment with biologics. Number of patients treated with each biologic were 39, 28, 19, 17, 26, and 17 patients treated with abatacept, adalimumab (ADA), etanercept, golimumab, infliximab (IFX), and tocilizumab, respectively. CXCL13 was measured by ELISA kit (Quantikine human CXCL13, R&D systems) for patients treated with ADA and IFX before and 24 weeks after treatment. The patients were classified into 61 responders (good) and 85 non-responders (moderate and none) by ACR/EULAR definition of remission criteria weeks after treatment. Results: Serum MMP-3 before the treatment was significantly increased in 146 RA patients as compared with 196 healthy subjects (196.0± 197.4 vs 58.6±27.4 ng/ml, p<0.001), and showed significant positive correlation with DAS28 (Rs=0.3842, p<0.001), but no significant difference was found between 61 responders (210.6±213 ng/ml) and 85 non-responders (185.6±186.3 ng/ml). As shown in Figure 1 (left), the MMP-3 levels gradually decreased 4, 12, and 24 weeks after successful treatment with biologics (p=0.04, p<0.001, and p<0.0001, respectively), and extent of the decrease were significantly bigger in responders than non-responders 12 and 24 weeks after treatment. Serum CXCL13 level before the treatment significantly correlated with MMP-3 levels (Rs =0.4648, p<0.001) as well as DAS28 (Rs =0.5182, p<0.001). After treatment with ADA, serum CXCL13 was significantly decreased after 24 weeks in responders as compared with non-responders (Figure 1 right, p<0.05). However, such difference was not found in patients treated with IFX. Patients with lower serum CXCL13 levels (<82.7 pg/ml) before the treatment were shown to become non-responders (p<0.07), especially their serum MMP-3 levels were low (<69.1 ng/ml). Conclusions: Serum MMP-3 and CXCL13 was shown to be useful as disease activity markers, and serial measurement were helpful to evaluate the effect of treatments with biologics. CXCL13 may be useful in evaluating and predicting the therapeutic outcome of some kinds of biologics. References: Mamehara A, et al: Kobe J Med Sci. 2010, 56(3): E98–107. Uemura Y, et al: Rinsho Byori. 2015, 63(12): 1357–1364 (Japanese). Meeuwisse CM, et al: Arthritis Rheum. 2011, 63(5): 1265–1273. Greisen SR, et al: Arthritis Res Ther, 2014, 16: 434. Acknowledgement: We thank Drs. Hitoshi Uga and Hirokazu Kurata of the Central Laboratories, Sysmex Co, Japan, for helpful discussion. Disclosure of Interest: S. Kumagai Consultant for: Sysmex Co, Y. Uemura: None declared, T. Saito: None declared, R. UMEDA: None declared, A. Muta: None declared, M. Izumi: None declared, K. Abe: None declared, S. Sendo: None declared, G. Tsuji: None declared